Metabolic risk factors, blood pressure and atherogenic indices of cardiovascular disease across different quartiles of dietary sodium to potassium ratio among young semi-professional athletes with overweight or obesity - Yisi Liu; Xin Wu; Liwei Sun (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Previous studies have revealed the role of the dietary sodium-to-potassium ratio in predicting cardiovascular and total mortality. However, a limited number of studies have investigated the association between the dietary sodium-to-potassium ratio and individual biomarkers of metabolic disease in athletes. In this study, we aimed to compare metabolic, atherogenic, and anthropometric risk factors for cardiovascular disease across different quartiles of the dietary sodium-to-potassium ratio among young semi-professional athletes with overweight or obesity. Methods In this cross-sectional study, 637 young semi-professional athletes, aged 20–40 years, were selected from active athletic and fitness clubs. Anthropometric measurements were performed, and fasting blood sugar, serum lipids, and lipoprotein (a) [Lp(a)] were measured. Atherogenic indices, including the atherogenic index of plasma (AIP), Castelli risk index (CRI)-I, CRI-II, and lipid tetrad index (LTI), were calculated. Results Participants in the highest quartile of the dietary sodium-to-potassium ratio were younger and had a higher waist-to-hip ratio (WHR) compared to those in the lowest quartile. Additionally, those in the highest quartile showed significantly higher serum total cholesterol and Lp(a) concentrations after adjusting for confounding factors (P < 0.05). Conclusion Our findings suggest that individuals in the higher quartiles of the dietary sodium-to-potassium ratio exhibit less favorable serum lipid profiles. Further longitudinal and interventional studies are needed to clarify the potential therapeutic role of reducing the dietary sodium-to-potassium ratio in managing cardiovascular disease risk factors.